Deep observations of the Type IIB flux landscape - A. Chauhan; M. Cicoli; S. Krippendorf; A. Maharana; P. Piantadosi; A. Schachner (Journal of High Energy Physics)
Abstract We present deep observations in targeted regions of the string landscape through a combination of analytic and dedicated numerical methods. Specifically, we devise an algorithm designed for the systematic construction of Type IIB flux vacua in finite regions of moduli space. Our algorithm is universally applicable across Calabi-Yau orientifold compactifications and can be used to enumerate flux vacua in a region given sufficient computational efforts. As a concrete example, we apply our methods to a two-modulus Calabi-Yau threefold, demonstrating that systematic enumeration is feasible and revealing intricate structures in vacuum distributions. Our results highlight local deviations from statistical expectations, providing insights into vacuum densities, superpotential distributions, and moduli mass hierarchies. This approach opens pathways for precise, data-driven mappings of the string landscape, complementing analytic studies and advancing the understanding of the distribution of flux vacua. This allows us to obtain different types of solutions with hierarchical suppressions, e.g. vacua with small values of the Gukov-Vafa-Witten superpotential |W 0|. We find an example with |W 0| = 5.547 × 10 −5 at large complex structure, without light directions and the use of non-perturbative effects.